Răspunsuri

2014-06-14T13:54:52+03:00
Expresia este:

=\sqrt{3}+\dfrac{\sqrt{6}}{\sqrt{3}}+\dfrac{\sqrt{6}}{\sqrt{2}}-\dfrac{4\sqrt{6}}{2\sqrt{2}}+\dfrac{4\sqrt{6}}{2\sqrt{3}}-3\sqrt{2}= \\  \\  \\ =\sqrt{3}+\sqrt{2}+\sqrt{3}-2\sqrt{3}+2\sqrt{2}-3\sqrt{2}= \\  \\  \\ =\underbrace{\left(\sqrt{3}+\sqrt{3}-2\sqrt{3}\right)}_{=0}+\underbrace{\left(\sqrt{2}+2\sqrt{2}-3\sqrt{2}\right)}_{=0}= \\  \\  \\ =0
a! și bineînțeles trebuie știut că √8 = 2√2 și că √12 = 2√3
mersii
cum ti-a dat 0 la prima paranteza?